2022
DOI: 10.1186/s42522-021-00057-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, diversity of diarrhoeagenic Escherichia coli and associated risk factors in well water  in Ile-Ife, Southwestern Nigeria

Abstract: Background Diarrhoeagenic Escherichia coli (DEC) strains are common causes of morbidity and mortality worldwide. Waterborne DEC could pose a health risk to humans through domestic use of contaminated water. However, epidemiological studies on DEC in well water are scarce in Nigeria. This study determined the prevalence, diversity and factors associated with the presence of DEC in well water in Ile-Ife, southwestern Nigeria. Methods We assessed 143 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Our findings of high diversity of E. coli in a marine environment are consistent with published studies of freshwater environments that have reported higher E. coli diversity utilizing the Shannon diversity index. A high degree of E. coli diversity was found in freshwater wells in Nigeria, which the authors speculated was due to multiple sources of contamination, including proximity to septic tanks and erosion (Odetoyin et al, 2022). Chandran and Mazumder (2015) described a high level of E. coli diversity, with seasonal variations, within a freshwater lake on Vancouver Island,…”
Section: Discussionmentioning
confidence: 99%
“…Our findings of high diversity of E. coli in a marine environment are consistent with published studies of freshwater environments that have reported higher E. coli diversity utilizing the Shannon diversity index. A high degree of E. coli diversity was found in freshwater wells in Nigeria, which the authors speculated was due to multiple sources of contamination, including proximity to septic tanks and erosion (Odetoyin et al, 2022). Chandran and Mazumder (2015) described a high level of E. coli diversity, with seasonal variations, within a freshwater lake on Vancouver Island,…”
Section: Discussionmentioning
confidence: 99%
“…Several outbreaks have highlighted fresh vegetables as potential vehicles of foodborne disease [9]. Although not in outbreak proportions, E. coli illnesses have also been reported in Southern Nigeria [10][11][12]. Its heightened concern over the spread of antimicrobial-resistant pathogens made this research imperative.…”
Section: Introductionmentioning
confidence: 99%